(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
In today’s rapidly developing market economy, where the economy and all sectors are undergoing digital transformation, the demand for high-quality representation of accounting information in financial reporting is steadily increasing. This is because such information serves as a primary source of data for management and economic decision-making. This, in turn, highlights the relevance of the present research topic. It is well known that in order to attract external financing, creditors and potential investors are primarily interested in a company’s property and financial position.